Affective factors and eustress-distress of nursing English students: A comparison analysis - Anwar, Khoirul; Maruf , Nirwanto; Arifani , Yudhi; Mansour, Marwa (Universitas Muhammadiyah Sidoarjo, 2023)
Studies outside of cognitive aspects, especially on psychological and affective factors, still have limited findings. In fact, these two issues contribute greatly to the success of English for Academic Purposes (EAP). This study aims to identify level of eustress-distress, anxiety-self-efficacy, and comparisons between these variables on learning performance of nursing students. This study used a mixed-method, a comparative study using closed and open questionnaires, and EAP reading test to 95 nursing students in the program of EAP. Certainly, the analysis used correlation and comparison tests using PLS-SEM and qualitative analysis of open questionnaires. The results showed that level of eustress-distress, and anxiety-self-efficacy of students were quite satisfactory. This means that students have ability to adapt positive reactions to learning pressure, more enthusiastic, and develop good self-confidence. Although distress does not influence self-efficacy and learning performance, it does have a significant impact on eustress. There is a strong impact and correlation between anxiety on self-efficacy, and self-efficacy on learning performance. So self-efficacy shows a strong moderating variable to bridge anxiety and learning performance. Qualitative findings also show that there are internal and external factors that contribute to the growth of eustress and self-efficacy. Further recommendations on these findings are also presented at the end of this study. HIGHLIGHTS: Affective factors are psychological constructs related to personality that impact foreign language mastery and provide benefits to language learning methodologies. Affect refers to feelings or emotions, including anxiety, self-esteem, motivation, attitude, and personality traits. The affective factors that influence language input are often referred to as "affective filters.” Eustress is an adaptation process in which an organism survives by changing its behavior and circumstances, to increase buffer zone, and result in an increase in the body's adaptive abilities. In simple terms, eustress is a positive adaptive response to a stressor by individuals. Distress is an unpleasant or negative emotional reaction to stress. Often students experience stress and psychological pressure due to an increase in burden of academic performance and personal factors, for example associating with new peer groups.